Evolutionary and Expression Analyses of the Apple Basic Leucine Zipper Transcription Factor Family - Zhao, Jiao; Guo, Rongrong; Guo, Chunlei; Hou, Hongmin; Wang, Xiping; Gao, Hua (Frontiers in Plant Science, 2016)
Transcription factors (TFs) play essential roles in the regulatory networks controlling many developmental processes in plants. Members of the basic leucine (Leu) zipper (bZIP) TF family, which is unique to eukaryotes, are involved in regulating diverse processes, including flower and vascular development, seed maturation, stress signaling and defense responses to pathogens. The bZIP proteins have a characteristic bZIP domain composed of a DNA-binding basic region and a Leu zipper dimerization region. In this study, we identified 112 apple (Malus domestica Borkh) bZIP TF-encoding genes, termed MdbZIP genes. Synteny analysis indicated that segmental and tandem duplication events, as well as whole genome duplication, have contributed to the expansion of the apple bZIP family. The family could be divided into 11 groups based on structural features of the encoded proteins, as well as on the phylogenetic relationship of the apple bZIP proteins to those of the model plant Arabidopsis thaliana (AtbZIP genes). Synteny analysis revealed that several paired MdbZIP genes and AtbZIP gene homologs were located in syntenic genomic regions. Furthermore, expression analyses of group A MdbZIP genes showed distinct expression levels in ten different organs. Moreover, changes in these expression proﬁles in response to abiotic stress conditions and various hormone treatments identified MdbZIP genes that were responsive to high salinity and drought, as well as to different phytohormones.